PERANCANGAN PROSEDUR SID/STAR RNAV 1 SEAHORSE AIRPORT SEBAGAI INOVASI PEMBELAJARAN PERFORMANCE-BASED NAVIGATION - Rosmayanti, Lina; Sonhaji, Imam; Pradana, Aminarno Budi; Wijaya, Syaiful Adhib (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
In air traffic control, the application of Performance Based Navigation (PBN) covers the areas of Aerodrome Control Tower, Approach & Area Control Procedure, Approach Control Surveillance, and Area Control Surveillance. Currently there is no PBN procedure available at the air traffic control simulation airport, namely Seahorse Airport. The aim of this research is to design the Performance Based Navigation SID/STAR RNAV 1 Seahorse Airport procedure as a medium for simulating flight traffic piloting practices. The research method used is the research and development method with reference to the method established by the International Civil Aviation Organization (ICAO) in Document 9906 Quality Assurance for Flight Procedure Design. The research stage begins with preliminary research/initiation to determine potential problems and needs analysis and review by stakeholders. The next stage is designing or designing procedures by collecting data on navigation coordinates, waypoints and obstacle charts sourced from the Seahorse Airport Standard Operating Procedure (SOP), then validating the design by the Safety Quality Manager & flight procedure design experts. At the initiation stage (need assessment), it was found that the need to increase special training and education related to PBN, especially at PPI Curug, was very urgent, namely 71.4%. Likewise, a review by stakeholders stated that the design was feasible. The safety assessment by the Safety Quality Manager was declared appropriate referring to aviation safety aspects. The validation results by flight procedure design experts stated that the SID/STAR RNAV 1 Seahorse Airport Procedure Performance Navigation procedure was suitable for use as a flight procedure. ABSTRAKDalam pemanduan lalu lintas penerbangan, penerapan Performance Based Navigation (PBN) mencakup pada bidang Aerodrome Control Tower, Approach & Area Control Procedural, Approach Control Surveillance, dan Area Control Surveillance. Saat ini belum tersedia prosedur PBN pada bandar udara simulasi pemanduan lalu lintas penerbangan yaitu Seahorse Airport. Tujuan penelitian ini adalah merancang prosedur Performance Based Navigation SID/STAR RNAV 1 Seahorse Airport sebagai media simulasi praktik pemanduan lalu lintas penerbangan. Metode penelitian yang digunakan adalah metode research and development dengan mengacu pada metode yang telah ditetapkan International Civil Aviation Organization (ICAO) dalam Document 9906 Quality Assurance for Flight Procedure Design. Tahap penelitian diawali dengan penelitian pendahuluan/initiation untuk mengetahui potensi masalah dan analisis kebutuhan serta review oleh pemangku kepentingan /stakeholder. Tahap berikutnya adalah perancangan atau design prosedur dengan mengumpulkan data-data koordinat navaids, waypoint, dan obstacle chart yang bersumber dari Standard Operating Procedure (SOP) Seahorse Airport, kemudian validasi design oleh Safety Quality Manager & pakar perancang prosedur penerbangan. Pada tahap inisiasi (need assessment), ditemukan bahwa kebutuhan untuk meningkatkan pelatihan dan pendidikan khusus terkait PBN, terutama di PPI Curug, sangat mendesak yaitu sebesar 71,4%. Begitu pula review oleh pemangku kepentingan menyatakan bahwa rancangan layak. Safety assessment (asesmen keselamatan) oleh Safety Quality Manager dinyatakan layak mengacu pada aspek keselamatan penerbangan. Hasil validasi oleh pakar perancang prosedur penerbangan dinyatakan bahwa prosedur Procedure Performance Navigation SID/STAR RNAV 1 Seahorse Airport layak untuk dipergunakan sebagai prosedur penerbangan.